Dielectric Loss Mechanism in Electromagnetic Wave Absorbing Materials - Qin, Ming; Zhang, Limin; Wu, Hongjing (Advanced science, 2022)
Electromagnetic (EM) wave absorbing materials play an increasingly important role in modern society for their multi‐functional in military stealth and incoming 5G smart era. Dielectric loss EM wave absorbers and underlying loss mechanism investigation are of great significance to unveil EM wave attenuation behaviors of materials and guide novel dielectric loss materials design. However, current researches focus more on materials synthesis rather than in‐depth mechanism study. Herein, comprehensive views toward dielectric loss mechanisms including interfacial polarization, dipolar polarization, conductive loss, and defect‐induced polarization are provided. Particularly, some misunderstandings and ambiguous concepts for each mechanism are highlighted. Besides, in‐depth dielectric loss study and novel dielectric loss mechanisms are emphasized. Moreover, new dielectric loss mechanism regulation strategies instead of regular components compositing are summarized to provide inspiring thoughts toward simple and effective EM wave attenuation behavior modulation. Electromagnetic wave loss mechanism investigation for dielectric absorbing materials is of great importance to guide the preparation of novel high‐performance absorbers. This review provides comprehensive insights into dielectric loss mechanisms and clarifies some misunderstandings and ambiguous concepts for each mechanism. In‐depth dielectric loss study and novel dielectric loss mechanisms regulation strategies are also highlighted.